Chemically Modulated Graphene Diodes - DUESBERG, GEORG (My University, 2013)
We report the manufacture of novel graphene diode sensors (GDS), which are composed of monolayer graphene on silicon substrates, allowing exposure to liquids and gases. Parameter changes in the diode can be correlated with charge transfer from various adsorbates. The GDS allows for investigation and tuning of extrinsic doping of graphene with great reliability. The demonstrated recovery and long-term stability qualifies the GDS as a new platform for gas, environmental, and biocompatible sensors.
PUBLISHED
Keywords: novel graphene diode sensors; novel graphene diode sensors